ANALISIS YURIDIS PENCURIAN SEPEDA MOTOR YANG DILAKUKAN OLEH ANAK UNTUK MEWJUDKAN PERLINDUNGAN HUKUM (STUDI PENELITIAN DI POLSEK BENGKONG KOTA BATAM) - Mella Dellia Marsudi Putri; Kaspol Jihad; Lia Fadjriani (Ensiklopedia of Journal, 2022)
Motorcycle theft is the most common theft in the life of the people of Batam, especially in the Bengkong area, because the object of theft is easy to find. Motorcycle theft that often occurs is not only done by adults, but also by children. Motorcycle theft by children raises problems regarding what factors cause children to commit the crime of motorcycle theft, how to overcome them. This study discusses the legal arrangements for the protection of children as perpetrators of crime. and how the implementation, constraints and solutions related to the investigation of the criminal act of motorcycle theft by children at the Bengkong Police Station in Batam city. This study uses normative and empirical methods where data collection is used by approaching the relevant laws and regulations, and conducting direct interviews with the police chief and the head of the Criminal Investigation Unit. The results of the research conducted by the author show that the legal arrangements carried out by the Bengkong Police in Batam are in accordance with the rules. but related to the investigation of the lack of adequate facilities. The suggestions in this study are the Bengkong police officers continue to improve their performance in protecting the community and maintain good relations with related institutions in handling children as well as increasing the number of personnel and supporting facilities to conduct investigations against children.